Sewaka Darma: Pembelajaran Keutamaan Kehidupan dan Implikasi Pedagogisnya - Siswantara, Yusuf (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2016)
Education has been developed in the western part as well as in the eastern part of the world, although each might have brought forth quite different methods and values. Education also has evolved in Indonesia since long before the contemporary systems. Sewaka Darma, an ancient Sundanese text, contains a particular model of education by way of teaching the wisdom of life. This text inspires further discussion on how education has been understood long time ago in its particular Sundanese context. Sewaka Darma is a kind of textbook for teaching that contains discourses between a teacher and his or her student. The teacher presents the teachings in a form of kawih (advice). By implementing a narrative model, the teacher conveys philosophy of life, the way of perfection, and moksha. The core of these teachings could be summarized: (a) that life is about suffering, being mortal, and a temporary condition, and (b) that life moves towards the perfection in moksha. On the level of practical everydayness, in order to gain perfection human strives to be a knowing and integral person. Sewaka Darma shows particular educational elements, that is, (a) virtue teachings for the sake of finding the basis of life through a spiritual outlook and (b) virtue advices that insinuate a learning methodology: on the wholeness and integrity of the self, on the character education by way of nyantrik (to be a follower in order to learn) method, on teachers as the role-model, and on the educational community.